<span>part A:
Let
t = total the liquid in the bottle including lemon juice and water
so t = lemon juice + water ( w = water, l = lemon juice) so t = l + w
but the bottle has 1 liter of water. and <span>60% lemon juice
</span>contains 60% lemon juice = 0.6, so l = 0.6t and w(water ) = 1 liter
t = l + w
substitute l = 0.6t and w = 1 into t = l + w
now you have equation
t = 0.6t + 1
part B:
from part A, you have equation t = 0.6t +1
solve for t
t = 0.6t +1
subtract 0.6t on both sides
t - 0.6t = 0.6t - 0.6t + 1
simplify
0.4t = 1
divide both sides by 0.4
0.4t/0.4 = 1/ 0.4
simplify
t = 2.5
2.5 liters is total including lemon juice and water
2.5 - 1(1 liter of water) = 1.5 <span>1 liter of lemon juice</span></span>
Answer:
H) B= 13
Step-by-step explanation:
<em>5 + b = 18</em>
<em>F) 5 + 5 = 10 so not equal to 18. It is not a solution</em>
<em>H) 5 + 13 = 18 it's equal . so it is the solution</em>
<em>G) 5 + 8 = 13 so not equal to 18. It is not a solution</em>
<em>J) 5 + 23 = 28 so not equal to 18. It is not a solution</em>
I am putting this into rows. Ex: row one has 0. row two has blank and seven.
1: 0
2: 9 7
3: - 9 6
4: 1 3
5: - 1 2
6: 1
So the answer on top would be 8 1 r 1.
Answer:
The answer is 1/x-3
Step-by-step explanation:
2/x−3+3/x+2−(4x−7/x2−x−6)
=x+2/x²−x−6
=x+2/(x+2)(x−3)
=1/x−3